2003
DOI: 10.1007/s00259-002-1037-5
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive imaging of tumor hypoxia in rats using the 2-nitroimidazole 18F-EF5

Abstract: Tumor hypoxia is an important prognostic indicator for cancer therapy outcome. EF5 [2-(2-nitro-1[ H]-imidazol-1-yl)- N-(2,2,3,3,3-pentafluoropropyl)-acetamide] has been employed to measure tumor hypoxia in animals and humans using immunohistochemical methods. EF5 is a lipophilic molecule designed to have a very uniform biodistribution, a feature of obvious benefit for use in PET imaging. The present study represents the first demonstration of noninvasive PET imaging of rat tumors using fluorine-18 labeled EF5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
86
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 26 publications
1
86
0
Order By: Relevance
“…Two clinically relevant "invasive" methods are needle electrodes techniques and 2-nitroimidazole binding studies, but the former can seldom be used in primary tumors of the head and neck. For the latter, the 2-nitroimidazole adduct formation in hypoxic cells can be assayed using immunohistochemistry (IHC), flow cytometry (FCM) and/or PET imaging (for example [13][14][15][16][17] ).…”
Section: Introductionmentioning
confidence: 99%
“…Two clinically relevant "invasive" methods are needle electrodes techniques and 2-nitroimidazole binding studies, but the former can seldom be used in primary tumors of the head and neck. For the latter, the 2-nitroimidazole adduct formation in hypoxic cells can be assayed using immunohistochemistry (IHC), flow cytometry (FCM) and/or PET imaging (for example [13][14][15][16][17] ).…”
Section: Introductionmentioning
confidence: 99%
“…18 F-fluoromisonidazole ( 18 F-FMISO) (13), 18 F-fluoroerythronitroimidazole (14), 18 F-fluoroazomycin arabinoside (15), and 18 F-fluoroetanidazole have been used with varying success as PET probes for hypoxia imaging, but only 18 F-FMISO is available in more than a few of the centers worldwide. However, a new group of etanidazole-based compounds, >2-(2-nitroimidazol-1 H-y)-N-(3-flouropropyl)acetamide (EF1) (16), 2-(2-nitroimidazol-1 H-y)-N-(3,3,3-tryflouropropyl)acetamide (EF3), and EF5 (17)(18)(19), has been developed both as biopsy-based (20) and as PET-based agents, and 18 F-EF5 has been synthesized by Dolbier et al (17) as well as at our center.…”
mentioning
confidence: 99%
“…Despite evidence, it is still not substantiated whether Cu-ATSM represents hypoxia. Further, 18 F-EF5, 2-(2-nitro-1[H]-imidazol-1-yl)-N-(2,2,3,3,3-pentafluoropropyl)-acetamide, was first tested in an animal study by Ziemer [55]. Evens et al found that EF5 uptake correlated with a poor prognosis in glioma patients [18].…”
Section: Discussionmentioning
confidence: 99%